Associations between pain, health, and lifestyle factors in 10-year-old boys and girls from a Swedish birth cohort - Julia S. Malmborg; Josefine Roswall; Gerd Almquist-Tangen; Jovanna Dahlgren; Bernt Alm; Stefan Bergman (BMC, 2023)
Abstract Background Pain is common in children and its associations with various biopsychosocial factors is complex. Comprehensive pain assessments could contribute to a better understanding of pediatric pain, but these assessments are scarce in literature. The aim of this study was to examine differences in pain prevalence and pain patterns in 10-year-old boys and girls from a Swedish birth cohort and to study associations between pain, health-related quality of life and various lifestyle factors stratified by sex. Methods 866 children (426 boys and 440 girls) and their parents from the "Halland Health and Growth Study" participated in this cross-sectional study. Children were categorized into two pain groups, "infrequent pain" (never-monthly pain) or "frequent pain" (weekly-almost daily pain), based on a pain mannequin. Univariate logistic regression analyses, stratified by sex, were performed to study associations between frequent pain and children's self-reports of disease and disability and health-related quality of life (Kidscreen-27, five domains), and parents' reports of their child's sleep (quality and duration), physical activity time, sedentary time, and participation in organized physical activities. Results The prevalence of frequent pain was 36.5% with no difference between boys and girls (p = 0.442). Boys with a longstanding disease or disability had higher odds of being in the frequent pain group (OR 2.167, 95% CI 1.168-4.020). Higher scores on health-related quality of life in all five domains for girls, and in two domains for boys, was associated with lower odds of being categorized into the frequent pain group. Frequent pain was associated with poor sleep quality (boys OR 2.533, 95% CI 1.243-5.162; girls OR 2.803, 95% CI 1.276-6.158) and more sedentary time (boys weekends OR 1.131, 95% CI 1.022-1.253; girls weekdays OR 1.137, 95% CI 1.032-1.253), but not with physical activity. Conclusions The high prevalence of frequent pain needs to be acknowledged and treated by school health-care services and the healthcare sector in order to prevent pain from influencing health and lifestyle factors negatively in children.